The Cumulative Burden Borne by Offspring Whose Mothers Were Sexually Abused as Children: Descriptive Results From a Multigenerational Study - Noll, Jennie G. (2008)
This multigenerational study empirically demonstrates the extent to which offspring whose parents experienced childhood abuse are at increased risk of being abused or neglected. Females with substantiated childhood sexual abuse and nonabused comparison females were assessed at six points spanning 18 years in a prospective, longitudinal study. Nonabusing parents or caregivers and offspring were also assessed. Descriptive results indicate that offspring born to mothers with histories of sexual abuse were more likely to be born preterm, have a teenage mother, and be involved in protective services. Abused mothers were more likely to be high-school dropouts, be obese, and have experienced psychiatric problems, substance dependence, and domestic violence. Results provide evidence for the advantages of intervention and prevention programs for victims of childhood maltreatment and their families. Primary prevention/intervention efforts extending throughout development and focusing on the cumulative risk to offspring will likely improve victim outcomes and curtail intergenerational transmission of adversity.